Perancangan Sistem Pengereman Mobil Menggunakan Mamdani Fuzzy Logic Control - Illa Rizianiza; Alfian Djafar (SPECTA Journal of Technology, 2017)
Increase in the number of vehicles, especially cars can increase the chances of accidents. Accidents happen because caused by several factors, including human error, environmental and technical vehicle. Human error factor caused by the driver of the vehicle less focus so less appropriate in decision making at the time of driving. Therefore, vehicles that have technology that can reduce the occurrence of accidents. One technology of a potential car vehicle to be developed in order to reduce the number of accidents is the technology of the brakingsystem. Car braking system is the most important safety system that it has. This paper provides an automatic car braking system using Mamdani Fuzzy Logic Control. This car braking system consist of two inputs and one output. Inputs are car position and car velocity. Car position represents the distance of the car from the obstacle detected and velocity represents the velocity of the car towards the obstacle. This output is brake that represents the car force to stop the car. The inputs use five membership funtions and the output use three membership functions. The car braking system designed uses twenty five rules. Performance analysis of the braking system is carried out on the braking system's ability to avoid obstacles. The result is the vehicle can brake at a distance 30m vehicle from the obstacle. The vehicle braking system began to brake the vehicle at 2.5 s with 9263 N up to 3.7 s.